Legal Effectiveness of Article 492 of the New Criminal Code in Addressing Digital Fraud Against MSMEs in Banjarmasin - Dadang Abdullah; Abdul Halim Barkatullah; Tavinayati Tavinayati; Andi Asari (UNISSULA, 2025)
The digital era has transformed the business landscape of traditional market traders and MSMEs in various regions, presenting new opportunities while also increasing the risk of online fraud. This study aims to analyse the effectiveness of Article 492 of the New Criminal Code in tackling digital fraud and protecting vulnerable small business actors. The method used is qualitative with a descriptive-analytical approach, combining normative legal studies and empirical data from interviews with market traders, MSME associations, cybercrime apparatus, and representatives of e-commerce platforms. This study analyzes primary legal sources, such as Article 492 of the New Criminal Code. The results of the study reveal a significant knowledge gap, with 75% of respondents being unaware of Article 492’s existence. The four main factors of vulnerability identified are low digital literacy, limited access to legal information, weak coordination with law enforcement officials, and dominance of large e-commerce platforms. To overcome this, this study offers a three-pillar coordination model, namely law enforcement, improving legal and digital literacy, and an application-based integrated reporting system. These findings confirm that effective digital criminal law requires not only regulation, but also cross-sector synergy and stronger public legal awareness.